‘Two in One’ Cloning Vector Applied for Blunt-End and T-A Cloning with One-Step Digestion–Ligation and Screening of Positive Recombinants by Unaided Eyes - Xingli Zhang; Chong Teng; Kaidi Lyu; Shanhua Lyu; Yinglun Fan (Current Issues in Molecular Biology)
To clone DNA sequences quickly and precisely into plasmids is essential for molecular biology studies. Some cloning vectors have been developed for the cloning of PCR products, including blunt-end and T-A cloning. However, different plasmids are required for the cloning of PCR products with blunt ends and 3′ A overhang ends. Here, a novel cloning vector, pYFRed, which is based on the pUC19 backbone, has emerged and can be applied in both blunt-end and T-A cloning. PCR products can be cloned into the pYFRed by a one-step digestion–ligation reaction in a tube. The endonuclease recognition sequences of SmaI, Eco53kI, EcoRV, PmeI, and SwaI for blunt-end cloning and XcmI for T-A cloning were designed and added between the lac promoter and the starting codon ATG of the mScarlet-I gene of pYFRed. The ligation efficiency was significantly higher because the restriction enzyme sites utilized were removed from the vector after being successfully constructed. The mScarlet-I gene was introduced into the pYFRed for the screening of the positive recombinants by the unaided eye without the need for additional reagents/equipment. pYFRed is easy to construct in an ordinary laboratory, which facilitates researchers to develop their cloning vector without purchasing commercial cloning vectors.